Functions of English and Latin in the Parliament of Finland 1970-2020 - Ristilä, Anna (Norway, 2026)
The Finnish parliament, eduskunta, operates in two national languages, Finnish and Swedish. Other languages, such as English and Latin, are also present in the plenary speeches in trace amounts. This paper explores the functions English and Latin may have in eduskunta, and contemplates whether they are used as elite closure, and if so, in what contexts. The questions are approached with quantitative and qualitative methods: first the use cases of English and Latin in the plenary speeches of the Finnish parliament between 1970 and 2020 are quantified, then ten possible intended functions for English and Latin use are identified by close reading the immediate contexts of each use case. Finally, the distributions of the use cases and their functions along topics are examined, and the possibility that English and Latin could be used as tools of elite closure is discussed.
Digital Parliamentary Data in Action (DiPaDA 2024) workshop